Sharing bedtimes : an illustrative exploration of children's bedtime reading rituals - Zhang, Qi Yin (2013)
This report discuss about the research topic on children bedtime reading ritual for my final year project. Analysing research findings of the ritual and the problems. Methodologies are also discuss and carry out for supporting these findings and for investigation. The discussion of the subject actually started from my observation that children bedtime reading is getting lesser practice or not practice at all with the busier lifestyle in the modern society. Findings indicates other results such as work pressure, laziness and several more. Children Bedtime reading however are actually very beneficial and influential upon child development. To name a few, such as children attachment needs, nurturing values, parents-child relationship level. This negligence of its importance make me feel there is a need to address and remind this meaningful ritual for the family. Therefore, this project aims to encourage and promote the valuable ritual of bedtime reading, also acting as a reminder to parents of the significant role it plays in a child's development and parent-child bonding.